The Influence Of Mathematical Modeling Learning Towards Complex Problem Solving - Nuhyal Ulia; Stevanus Budi Waluya; Isti Hidayah; Emi Pudjiastuti (International Conference on Science, Education, and Technology, 2022)
Complex problem solving (CPS) as a new paradigm in solving problems is one often he the ten soft skills that need to be possessed in facing the Industrial Revolution 4.0 and even becomes essential because it ranks at the top of the list of job requirements in the 21st century. The CPS indicators include (1) collecting information systematically, (2) diagnosing problems by integrating the most relevant information, (3) finding potential solutions by building an appropriate model of the problem structure, and (4) determining solutions and implementing them. Mathematical modeling as a model of teaching mathematics aims to read, interpret, formulate and solve specific problems. The steps of learning Mathematical modeling consist of the identification stage, the stage of determining the mathematical model, the stage of determining the solution of the model, and the interpretation of the model solution. This study aimed to examine the effect of mathematical modeling learning on CPS. This study uses a test technique with data analysis techniques paired sample t-test. The results showed an effect of Mathematical modeling learning on CPS, which was indicated by the difference in the CPS abilities of elementary school teacher candidates before and after mathematical modeling learning. From the results of the SPSS test, the value of sig. (2-tailed): 0.000 < 0.005 on the paired sample t-test results so that Ha is accepted, meaning there are differences in CPS before and after mathematical modeling learning. Mathematical modeling learning has a role in helping elementary school teacher candidates to solve complex problems.